BASE KEYS FOR AN ETHICS IN THE RELATIONSHIP WITH AI ENTITIES - barraca mairal, javier (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
This text explores the essential anthropological bases on which the ethics related to AI are founded. It does so based on the conviction that any deontology related to AI must be based on a deep understanding of its foundations. To this end, it begins by delving into the need to establish a humanist framework in which to adequately situate the interactions between human subjects with AI entities and systems. The centrality of the concrete person plays here a cardinal ethical place. Next, several ethical keys relevant to the relationships between humans and AI are proposed. Among them are the need to make nuclear distinctions regarding these realities and humans, in order to adequately respect personal dignity. Also, it is warned about the care that has to be paid in attention to the consequences derived from the modification of our intellectual habits due to the use of AI in terms of the treatment of information and its empathic appearance. And it is prevented from the effects of these issues for individual and collective security.
Keywords: AI, ethics, personal dignity, appearance, prudence